Preoperative CBCT Guided Bone Regeneration Combined with Concentrated Growth Factor Applied in the Implantation of Maxillary Teeth with Insufficient Bone Mass: Preoperative CBCT Guided Bone Regeneration - Men, Bei; Yang, Huaiyi; Zhang, Jie (Cellular and Molecular Biology, 2022)
It was to explore the application effect of cone beam computed tomography (CBCT) guided bone regeneration (GBR) combined with concentrated growth factor (CGF) in the implantation of maxillary teeth with insufficient bone mass. 78 patients with single maxillary anterior tooth loss and labial alveolar defects in Dazhong Stomatological Hospital were retrospectively analyzed and randomly divided into groups A and B. Both groups were treated with surgical methods of GBR at the same time of implantation. Group A: CGF fibrin fluid and Bio-Oss bone powder, covered with CGF membrane on the surface to guide bone regeneration. Group B: Bio-Oss bone powder was implanted and covered with Heal All collagen biofilm. The horizontal bone width, keratinized gingival width, bone plate thickness, implant margin results, and alveolar ridge width were analyzed at 3 and 6 months before and after the operation in both groups. 6 months after the operation, the difference in the indexes between the two groups was evident; and in group A, the indexes had an obvious difference in contrast with those before operation; the healing rate of soft tissue was 100% in group A and 80% in group B, which was significantly different (P < 0.05). Preoperative CBCT GBR combined with CGF can promote the bone formation content of guided regeneration of bone defects in the maxillary teeth region.